2018
DOI: 10.1021/acsomega.8b02155
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Decarbonylative Alkylation of Aroyl Fluorides Assisted by Lewis-Acidic Organoboranes

Abstract: Herein, nickel-catalyzed decarbonylative C–F bond alkylation of aroyl fluorides with organoboron reagents is reported. Aroyl fluorides are more chemically stable than the corresponding aroyl chlorides and can be readily synthesized from the corresponding carboxylic acids. The fluoronickel intermediate formed via oxidative addition interacts with Lewis-acidic trialkylboranes, and the subsequent decarbonylative alkylation proceeds. This new synthetic methodology allows 1,2-bifunctionalization of aromatic carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 93 publications
1
28
0
2
Order By: Relevance
“…[14] Soon after, the same group reported an ickel-catalyzed decarbonylative borylation of acid fluorides 4 (Scheme 5). As imilar strategy has been used for the decarbonylative methylation or ethylation of acid fluoride using Lewis acidic trimethyl-or triethylborane and ac losely related catalytic system (Ni(cod) 2 /dppe), which suffers from anarrower scope.…”
Section: Methodsmentioning
confidence: 99%
“…[14] Soon after, the same group reported an ickel-catalyzed decarbonylative borylation of acid fluorides 4 (Scheme 5). As imilar strategy has been used for the decarbonylative methylation or ethylation of acid fluoride using Lewis acidic trimethyl-or triethylborane and ac losely related catalytic system (Ni(cod) 2 /dppe), which suffers from anarrower scope.…”
Section: Methodsmentioning
confidence: 99%
“…Transition‐metal‐catalyzed cross‐coupling reactions of acyl electrophiles with aryl nucleophiles represent a powerful and reliable synthetic strategy for the introduction of acyl fragments into aromatic rings to provide aromatic ketones, and a large variety of carboxylic acid derivatives are currently used as acyl electrophiles . Among these, acyl fluorides have recently gained much attention as valuable carbon‐based electrophiles in cross‐coupling reactions, especially in acyl coupling and decarbonylative coupling reactions . Due to the moderate electrophilicity of acyl fluorides, they exhibit a good balance between stability and reactivity with respect to their compatibility under nucleophilic conditions, that is, they are more stable than the commonly employed acyl chlorides, yet more reactive than the corresponding esters and amides .…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Amongt hese, acyl fluorides have recently gained much attention as valuablec arbon-based electrophiles in cross-couplingreactions, especially in acyl coupling [14][15][16][17] and decarbonylative coupling reactions. [17][18][19][20][21][22] Due to the moderate electrophilicity of acyl fluorides,t hey exhibit ag ood balance between stability and reactivity with respectt ot heir compatibility under nucleophilic conditions, that is, they are more stable than the commonly employed acyl chlorides, [4] yet more reactive than the corresponding esters [9, 13b] and amides. [5-9, 11,13e] In fact, acyl fluorides are isolable using column chromatography on silica gel andc an be used without any special precautions against moisture.…”
mentioning
confidence: 99%
“…With the optimized condition in hand (entry 16 in Table ), the substrate scope was surveyed (Scheme ). Acyl fluorides were readily prepared from the corresponding carboxylic acids or acyl chlorides . It was found that acyl fluorides with an extended‐conjugated system ( 1 a , c , d ) reacted without difficulty, providing stannylation products in 77–89% isolated yields.…”
Section: Methodsmentioning
confidence: 99%